Pretreated sand, precoated sand and preparation method thereof

The sand is treated with high-temperature surfactant and coupling agent, and combined with an appropriate amount of resin and reinforcement, a coated sand with high heat strength and high crumbness is prepared, which solves the problems of low thermal strength and poor crumbness in the prior art, and meets the lightweight demand of automotive parts.

CN119702947APending Publication Date: 2025-03-28ZHANGWU COUNTY LIAN XIN FOUNDRY SILICON SAND

Patent Information

Application Number
CN202411886743.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the thermal strength of the coated sand is low and the curing speed is fast, which leads to poor deformation and dispersion of the sand core, making it difficult to meet the lightweight demand of automotive parts.

Method used

High surfactant pretreated sand is prepared by heating dry or regenerated sand to 800-1000°C for surface activation and spraying the coupling agent treatment solution. Then, the pretreated sand is mixed with raw materials such as phenolic resin, easy-to-decompose resin, lubricant, foaming agent, crumbing agent, curing agent and reinforcement to prepare a coated sand.

Benefits of technology

The connection strength between resin and sand is improved, the thermal strength and collapse properties of the coated sand are enhanced, the amount of resin added is reduced, the cost is reduced, and the core making efficiency and collapse properties after casting are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199516420000101
    Figure BDA0005199516420000101
Patent Text Reader

Abstract

The invention discloses pretreated sand, precoated sand and a preparation method of the precoated sand, and belongs to the technical field of molding material precoated sand for casting. The pretreated sand is prepared through the following steps that dried sand or regenerated sand is heated to 800-1000 DEG C for surface activation treatment, then cooling is conducted, coupling agent treating fluid is sprayed for surface treatment, and the pretreated sand is obtained. In addition, the invention further provides precoated sand which is prepared by mixing the following raw materials. The raw materials comprise the following components in parts by weight: 100 parts of pretreated sand, 0.5-1.5 parts of phenolic resin, 0-0.2 part of easily decomposed resin, 0.1-0.2 part of a lubricating agent, 0.1-1 part of a foaming agent, 0.02-0.1 part of a curing agent solution and 0.02-0.1 part of a collapsing agent. In addition, the invention further provides a preparation method of the precoated sand. According to the pre-treated sand provided by the invention, the connection strength between the resin and the sand is improved, so that the strength of the pre-treated sand is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coated sand as a molding material for casting, and in particular to pretreated sand, coated sand and a preparation method thereof. Background Art

[0002] Coated sand is a special sand with a layer of resin coated on the surface of the sand. Under heating or catalyst, the resin can be cross-linked and solidified. Coated sand has good fluidity, high specific strength, long storage period, and can be made into sand cores with complex shapes and high precision. It is widely used in the production of cast iron, cast steel and non-ferrous alloy castings.

[0003] In recent years, with the development of the automobile industry, higher requirements have been put forward for automobile lightweighting. Nonferrous alloys, especially aluminum alloys, are widely used in automobile parts. For example, the pouring temperature of thick aluminum alloy parts (motor housing, cylinder head, bracket) is relatively low, generally 670-750℃, and the sand core size is large. It is easy to have insufficient curing degree during core making, resulting in low thermal strength and deformation of sand core. During casting, the coated sand cannot be completely collapsed due to the low temperature. In order to meet the collapse requirements, the usual coated sand will reduce the amount of resin added, which leads to low strength of the sand core, easy core breakage during core making, and high breakage rate during the transportation of sand cores with insufficient strength.

[0004] Patent CN112296248A discloses an easily disintegrable coated sand, comprising the following raw materials by mass: 320-410 parts of silica sand for casting, 3.7-4.4 parts of thermoplastic phenolic resin, 1.1-1.5 parts of thermosetting resin, 3.5-4.3 parts of cooling water, 0.2-0.4 parts of calcium stearate, urotropine solution and disintegrating agent, wherein the disintegrating agent is a halogen compound and the mass fraction of the disintegrating agent is 0.01%-0.03% of the mass of the silica sand for casting. The halogen disintegrating agent is used to improve the disintegration property, and the action temperature of the halogen is relatively high.

[0005] Patent CN114799038B discloses a kind of easily disintegrating coated sand, which includes the following ingredients: silica sand, phenolic resin, curing agent hexamethylenetetramine, lubricant calcium stearate, and an easily disintegrating agent; the easily disintegrating agent includes calcium oxide and polyacrylate, and the easily disintegrating agent is 0.01-0.05% of the weight of the silica sand. The disintegrating property is improved by adding calcium oxide and polyacrylate.

[0006] Patent CN110586849B discloses an easily disintegrable resin coated sand. The raw material components of the coated sand include: sodium chloride and modified phenolic resin. Based on 100 parts by weight of the sodium chloride, the content of the modified phenolic resin is 2-5 parts by weight. The raw material components also include 0.2-1 parts by weight of a hardener, 0.08-0.3 parts by weight of calcium stearate, 0.1-0.5 parts by weight of a disintegrator, 0.5-1.5 parts by weight of coconut glucoside, and 0.1-1 parts by weight of an alkali metal oxide. The disintegration is improved by modifying the resin and adding the disintegrator, but the problems of low thermal strength and fast curing speed cannot be solved.

[0007] How to improve the thermal strength or disintegration of coated sand is a problem that the existing technology needs to solve. Summary of the invention

[0008] The purpose of the present invention is to overcome the above technical deficiencies, provide a pretreated sand, coated sand and a preparation method thereof, and solve the technical problem of how to improve the thermal strength of coated sand in the prior art.

[0009] In order to achieve the above technical purpose, the technical solution of the present invention provides a pretreated sand, which is prepared by the following steps: heating the dried sand or regenerated sand to 800-1000°C for surface activation treatment, then cooling, and spraying a coupling agent treatment liquid for surface treatment to obtain the pretreated sand.

[0010] In any embodiment, the dried sand or the regenerated sand is heated to 800-1000° C. and kept warm for 1-2 hours.

[0011] In any embodiment, the coupling agent treatment solution is obtained by mixing a coupling agent, ethanol and water.

[0012] In any embodiment, the coupling agent treatment liquid comprises, by weight, 5-10 parts of coupling agent, 10-15 parts of ethanol and 75-85 parts of water; and / or, the coupling agent is KH550.

[0013] In addition, the present invention also proposes a coated sand, which is prepared by mixing the following raw materials; the raw materials, calculated by weight, include: 100 parts of pretreated sand, 0.5-1.5 parts of phenolic resin, 0-0.2 parts of easily decomposable resin, 0.1-0.2 parts of lubricant, 0.1-1 parts of foaming agent, 0.8-1.5 parts of water, 0.02-0.1 parts of curing agent solution, 0.02-0.1 parts of disintegrating agent, 0.02-0.5 parts of reinforcing agent and 0.02-0.1 parts of coupling agent.

[0014] In any embodiment, the enhancer is one or more of dibutyl phthalate, polyethylene glycol, oxalic acid and pyrogallic acid; and / or, the foaming agent is one or more of starch, azodicarbonamide, p-toluenesulfonyl hydrazide, ammonium carbonate and potassium hydrogen tartrate; and / or, the lubricant is calcium stearate.

[0015] In any embodiment, the curing agent solution is an aqueous solution of hexamethylenetetramine.

[0016] In any embodiment, the mass concentration of the urotropine aqueous solution is 15-30%.

[0017] In any embodiment, the disintegrating agent is one or more of potassium nitrate, calcium peroxide and sodium percarbonate; and / or the easily decomposable resin is one or more of rosin, epoxy resin, terpene resin and vinyl resin.

[0018] In addition, the present invention also provides a method for preparing the coated sand, comprising the following steps: heating the pre-treated sand to 120-140° C., adding the pre-treated sand to a sand mixer, stirring and mixing, and starting timing;

[0019] 0S Adding foaming agent;

[0020] After 10-15 seconds, add phenolic resin and easily decomposable resin;

[0021] After 20-30 seconds, add the enhancer and disintegrator;

[0022] After 50-60 seconds, add curing agent solution;

[0023] Add lubricant after 100-130S;

[0024] After 150-170 seconds, coated sand is obtained.

[0025] Compared with the prior art, the beneficial effects of the present invention include: the pretreated sand proposed in the present invention is prepared by the following steps: heating the dried sand or the regenerated sand to 800-1000°C for surface activation treatment, then cooling, and spraying the coupling agent treatment liquid for surface treatment to obtain the pretreated sand. The sand pretreated with the high-temperature coupling agent has high surface activity, which improves the connection strength between the resin and the sand, makes the coated sand stronger, and reduces the amount of resin added. DETAILED DESCRIPTION

[0026] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0027] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0028] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0029] The present specific embodiment provides a pretreated sand, characterized in that it is prepared by the following steps: heating dried sand or regenerated sand to 800-1000°C and keeping it warm for 1-2h for surface activation treatment, then cooling, and spraying a coupling agent treatment liquid for surface treatment to obtain the pretreated sand; the coupling agent treatment liquid is obtained by mixing a coupling agent, ethanol and water; the coupling agent treatment liquid, calculated by weight, includes 5-10 parts of coupling agent, 10-15 parts of ethanol and 75-85 parts of water; in some embodiments, the coupling agent is KH550.

[0030] The present specific embodiment also provides a coated sand, which is prepared by mixing the following raw materials; the raw materials, calculated by weight, include: 100 parts of the above-mentioned pretreated sand, 0.5-1.5 parts of phenolic resin, 0-0.2 parts of easily decomposable resin, 0.1-0.2 parts of lubricant, 0.1-1 parts of foaming agent, 0.8-1.5 parts of water, 0.02-0.1 parts of curing agent solution, 0.02-0.1 parts of disintegrating agent, 0.02-0.5 parts of reinforcing agent and 0.02-0.1 parts of coupling agent; the reinforcing agent is diphthalic acid The invention relates to a method for preparing the present invention, wherein the present invention comprises: a first step of preparing the present invention and a second step of preparing the present invention; the ...

[0031] This specific embodiment also provides a method for preparing the coated sand, comprising the following steps: heating the pre-treated sand to 120-140° C., adding the pre-treated sand to a sand mixer, stirring and mixing, and starting timing;

[0032] 0S Adding foaming agent;

[0033] After 10-15 seconds, add phenolic resin and easily decomposable resin;

[0034] After 20-30 seconds, add the enhancer and disintegrator;

[0035] After 50-60 seconds, add curing agent solution;

[0036] Add lubricant after 100-130S;

[0037] After 150-170 seconds, coated sand is obtained.

[0038] The principle and effect of the coated sand proposed by the present invention are:

[0039] 1. The present invention uses sand pretreated with a high-temperature coupling agent, which has high surface activity, improves the connection strength between the resin and the sand, makes the coated sand stronger, and reduces the amount of resin added.

[0040] 2. The resin is added with easily decomposable resin, which decomposes prematurely when heated, interrupting the continuity of the resin and reducing the strength after casting.

[0041] 3. The reinforcing agent can improve the toughness of the coated sand, the acidic substance promotes curing and improves the thermal strength, reduces the amount of resin added, saves costs and improves disintegration.

[0042] 4. The foaming agent is added between the resin and the sand. When the sand core is subjected to high temperature, the phenolic resin can be foamed to improve the thermal strength and disintegration properties.

[0043] 5. The disintegrator used can release oxygen at high temperature to promote the decomposition of phenolic resin. The coated sand produced by the present invention has the advantages of high strength, fast curing speed and easy disintegration, which effectively solves the problems of low strength, broken cores during transportation, slow curing speed, low core making efficiency and poor disintegration after casting when using coated sand.

[0044] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0045] In the present invention, reference is made to “some embodiments”, “this embodiment”, examples, etc., which describe a subset of all possible embodiments, but it can be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.

[0046] If similar descriptions of "first / second" appear in the application documents, the following instructions are added. In the following description, the terms "first\second\third" are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It can be understood that "first\second\third" can be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that described herein.

[0047] In this embodiment, the term "and / or" is merely a description of the association relationship between associated objects, indicating that three relationships may exist. For example, object A and / or object B may represent three situations: object A exists alone, object A and object B exist at the same time, and object B exists alone.

[0048] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0049] Example 1

[0050] This embodiment provides a pretreated sand, which is prepared by the following steps: heating the dried sand to 800° C. and keeping it warm for 1 hour for surface activation treatment, then cooling it, and spraying a coupling agent treatment liquid for surface treatment to obtain the pretreated sand; the coupling agent treatment liquid is obtained by mixing a coupling agent, ethanol and water; the coupling agent treatment liquid, calculated by weight, includes 8 parts of coupling agent KH550, 10 parts of ethanol and 82 parts of water.

[0051] The present embodiment also proposes a coated sand, which is prepared by mixing the following raw materials; the raw materials, calculated by weight, include: 100 parts of pretreated sand, 1.5 parts of phenolic resin, 0.05 parts of rosin, 0.05 parts of terpene resin, 0.15 parts of lubricant calcium stearate, 0.1 parts of ammonium carbonate, 0.05 parts of starch, 0.8 parts of water, 0.08 parts of urotropine solution, 0.02 parts of potassium nitrate, 0.02 parts of polyethylene glycol, 0.01 parts of pyrogallic acid and 0.02 parts of coupling agent KH550; the mass concentration of the urotropine aqueous solution is 20%.

[0052] This embodiment also provides a method for preparing the coated sand, comprising the following steps: heating the pre-treated sand to 130° C., adding the pre-treated sand to a sand mixer, stirring and mixing, and starting timing;

[0053] 0S Adding foaming agent;

[0054] After 15 seconds, add phenolic resin and easily decomposable resin;

[0055] After 25 seconds, add the enhancer and disintegrator;

[0056] After 55 seconds, add curing agent solution;

[0057] Add lubricant after 120S;

[0058] After 170 seconds, coated sand is obtained.

[0059] Example 2

[0060] This embodiment proposes a pretreated sand, which is prepared by the following steps: heating the dried sand to 900° C. and keeping it warm for 1.5 hours for surface activation treatment, then cooling it, and spraying a coupling agent treatment liquid for surface treatment to obtain the pretreated sand; the coupling agent treatment liquid is obtained by mixing a coupling agent, ethanol and water; the coupling agent treatment liquid, calculated by weight, includes 5 parts of coupling agent KH550, 15 parts of ethanol and 75 parts of water.

[0061] The present embodiment also provides a coated sand, which is prepared by mixing the following raw materials; the raw materials, calculated by weight, include: 100 parts of pretreated sand, 0.5 parts of phenolic resin, 0.1 parts of epoxy resin, 0.05 parts of vinyl resin, 0.2 parts of lubricant calcium stearate, 0.1 parts of azodicarbonamide, 0.1 parts of p-toluenesulfonyl hydrazide, 1.0 parts of water, 0.02 parts of urotropine solution, 0.05 parts of sodium percarbonate, 0.02 parts of oxalic acid, 0.03 parts of dibutyl phthalate and 0.1 parts of coupling agent KH550; the mass concentration of the urotropine aqueous solution is 15%.

[0062] This embodiment also provides a method for preparing the coated sand, comprising the following steps: heating the pre-treated sand to 120° C., adding the pre-treated sand to a sand mixer, stirring and mixing, and starting timing;

[0063] 0S Adding foaming agent;

[0064] After 10 seconds, add phenolic resin and easily decomposable resin;

[0065] After 30 seconds, add the enhancer and disintegrator;

[0066] Add curing agent solution after 50S;

[0067] Add lubricant after 120S;

[0068] After 160 seconds, coated sand is obtained.

[0069] Example 3

[0070] This embodiment provides a pretreated sand, which is prepared by the following steps: heating the dried sand to 1000° C. and keeping it warm for 2 hours for surface activation treatment, then cooling it, and spraying a coupling agent treatment liquid for surface treatment to obtain the pretreated sand; the coupling agent treatment liquid is obtained by mixing a coupling agent, ethanol and water; the coupling agent treatment liquid, calculated by weight, includes 10 parts of coupling agent KH550, 12 parts of ethanol and 85 parts of water.

[0071] The present embodiment also proposes a coated sand, which is prepared by mixing the following raw materials; the raw materials, calculated by weight, include: 100 parts of pretreated sand, 1.0 parts of phenolic resin, 0.1 parts of rosin, 0.1 parts of vinyl resin, 0.1 parts of lubricant calcium stearate, 0.2 parts of ammonium carbonate, 0.1 parts of potassium hydrogen tartrate, 1.5 parts of water, 0.1 parts of urotropine solution, 0.1 parts of potassium nitrate, 0.1 parts of polyethylene glycol, 0.1 parts of oxalic acid and 0.05 parts of coupling agent KH550; the mass concentration of the urotropine aqueous solution is 15%.

[0072] This embodiment also provides a method for preparing the coated sand, comprising the following steps: heating the pre-treated sand to 140° C., adding the pre-treated sand to a sand mixer, stirring and mixing, and starting timing;

[0073] 0S Adding foaming agent;

[0074] After 12 seconds, add phenolic resin and easily decomposable resin;

[0075] After 20 seconds, add the enhancer and disintegrator;

[0076] Add curing agent solution after 50S;

[0077] Add lubricant after 130S;

[0078] After 160 seconds, coated sand is obtained.

[0079] Comparative Example 1

[0080] The difference between this comparative example and Example 1 is that the pretreated sand in the coated sand is replaced by dried sand, and the other raw materials, preparation methods and process conditions are the same as those in Example 1.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 1 is that the foaming agent ammonium carbonate and starch are not added, but the amount of the foaming agent is replaced by an equal amount of phenolic resin.

[0083] The various performance indicators of the easily disintegrated coated sand prepared in the above Examples 1-3 and Comparative Examples 1-2 were tested according to the "Coated Sand for Casting" JB / T8583-2008 standard, and the results are shown in Table 1.

[0084] Table 1 Test results of coated sand

[0085]

[0086] It should be noted that the residual strength test method is: the bending strength test block is placed at 550℃, kept warm for 5 minutes, and the strength is tested after cooling.

[0087] Collapse rate test method: weigh the bending strength test block, record it as M0, put it into 550℃, keep it warm for 5 minutes, put it on a 20-mesh screen for 20 seconds after cooling, and weigh the weight of the sand remaining on the 20-mesh screen M1. Collapse rate = (M0-M1) / M0*100%.

[0088] It can be seen from Table 1 that the coated sands of Examples 1-3 proposed by the present invention all have higher strength and higher dispersion rate.

[0089] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A pre-treated sand, characterized in that: The pre-treated sand is prepared by heating the dried sand or the regenerated sand to 800-1000°C for surface activation treatment, cooling the sand, and spraying a coupling agent treatment liquid for surface treatment to obtain the pre-treated sand.

2. The pretreated sand according to claim 1, characterized in that: The dried sand or the regenerated sand is heated to 800-1000° C. and kept warm for 1-2 hours.

3. The pretreated sand according to claim 1, characterized in that: The coupling agent treatment liquid is obtained by mixing a coupling agent, ethanol and water.

4. The pretreated sand according to claim 3, characterized in that: The coupling agent treatment liquid comprises, by weight, 5-10 parts of coupling agent, 10-15 parts of ethanol and 75-85 parts of water; and / or the coupling agent is KH550.

5. A coated sand, characterized in that: The invention is prepared by mixing the following raw materials; the raw materials, calculated by weight, include: 100 parts of the pretreated sand according to any one of claims 1 to 4, 0.5-1.5 parts of phenolic resin, 0-0.2 parts of easily decomposable resin, 0.1-0.2 parts of lubricant, 0.1-1 parts of foaming agent, 0.8-1.5 parts of water, 0.02-0.1 parts of curing agent solution, 0.02-0.1 parts of disintegrating agent, 0.02-0.5 parts of reinforcing agent and 0.02-0.1 parts of coupling agent.

6. The coated sand according to claim 5, characterized in that: The enhancer is one or more of dibutyl phthalate, polyethylene glycol, oxalic acid and pyrogallic acid; and / or the foaming agent is one or more of starch, azodicarbonamide, p-toluenesulfonyl hydrazide, ammonium carbonate and potassium hydrogen tartrate; and / or the lubricant is calcium stearate.

7. The coated sand according to claim 5, characterized in that: The curing agent solution is a hexamethylenetetramine aqueous solution.

8. The coated sand according to claim 7, characterized in that: The mass concentration of the hexamethylenetetramine aqueous solution is 15-30%.

9. The coated sand according to claim 5, characterized in that: The disintegrating agent is one or more of potassium nitrate, calcium peroxide and sodium percarbonate; and / or the easily decomposable resin is one or more of rosin, epoxy resin, terpene resin and vinyl resin.

10. A method for preparing coated sand according to any one of claims 5 to 9, characterized in that: The following steps are involved: Heat the pre-treated sand to 120-140℃, add it into the sand mixer, stir and mix, and start timing; 0S Adding foaming agent; After 10-15 seconds, add phenolic resin and easily decomposable resin; After 20-30 seconds, add the enhancer and disintegrator; After 50-60 seconds, add curing agent solution; Add lubricant after 100-130S; After 150-170 seconds, coated sand is obtained.

Citation Information

Patent Citations

  • A type of easily collapsible resin-coated sand

    CN110586849B

  • Easily collapsible precoated sand and preparation method thereof

    CN112296248A

Cited By

  • Epoxy colored sand floor coating containing melamine resin as well as preparation method and application of epoxy colored sand floor coating

    CN120310373A